Cerebrospinal fluid estradiol fluctuations during the estrous cycle and their association with intraocular pressure and optic nerve sheath diameter in dogs: a first report - Özcan, Candemir; Bozacı, Serkan; Soytürk, Berrak Işık; Tümer, Kenan Çağrı; Deniz, Ömer; Şafak, Tarık; Dellalbaşı, Ayşe Başak; Kaynar, Özgür; Dogan, Elif (Springer Science and Business Media LLC, 2025)
Abstract Objective The relationship between optic nerve sheath diameter (ONSD), an indicator of intracranial pressure (ICP), and intraocular pressure (IOP) is controversial. The two aims of this study were; first, to investigate the effect of cerebrospinal fluid (CSF) estradiol (E2) and progesterone (P4) levels on ONSD and second, to investigate the relationship between ONSD and IOP in female dogs. Methods IOP measurements were performed using rebound tonometer, and transpalpebral ultrasonographic assessment of the ONSD was conducted. CSF samples were collected, and E2 and P4 levels were quantified using enzyme-linked immunosorbent assay (ELISA). Multiple regression analysis was conducted to assess the relationships among the variables. Results Multiple regression analyses on dogs found that the level of cerebrospinal fluid estradiol level (CSF-E2) significantly influenced left (L) ONSD ( p  = 0.0421, R² = 0.1551) and right (R) ONSD ( p  = 0.0216, R² = 0.1938). Systolic blood pressure (SBP) was a significant independent variable for left intraocular pressure (LIOP) ( p  = 0.0122, R² = 0.2261), while body weight was a significant predictor for right intraocular pressure (RIOP) ( p  = 0.0008, R² = 0.3679). Conclusions This study revealed that CSF-E2 levels exert a significant influence on ONSD in dogs, whereas no direct association was observed between IOP and ONSD. These findings underscore the notion that ONSD is modulated not only by hemodynamic mechanisms but also by hormonal regulation.
Keywords: Research